A CASE WITH COMPLICATED DIAGNOSIS FOR DIFFUSE B-CELL LARGE CELL LYMPHOMA - E. I. Zyablova; J. V. Laktionova; J. V. Shevchenko; N. V. Agurina; E. P. Yasakova; O. N. Ponkina (Инновационная медицина Кубани)
Lymphomas are a heterogeneous group of diseases with various histological signs which are different in clinical course and prognosis. They all are divided into main groups: B-cell lymphoproliferative diseases, Т-cell lymphoproliferative diseases, Hodgkin disease. The first two groups (excluding leukoses) are defined as "non-Hodgkin lymphomas” (NHL). They are about 5–6% of all malignant neoplasms and in their structure they occupy the fifth position in overseas countries. In the present article we present a clinical case with diffuse B-cell large cell lymphoma of the small pelvis with retroperitoneal space infiltration, root of mesentery, small pelvis fat tissue.